2020
DOI: 10.34067/kid.0000212019
|View full text |Cite
|
Sign up to set email alerts
|

Can Behavioral Research Improve Transplant Decision-Making? A Mock Offer Study on the Role of Kidney Procurement Biopsies

Abstract: Background The use of procurement biopsies for assessing kidney quality has been implicated as a driver of the nearly 20% kidney discard rate in the United States. Yet in some contexts, biopsies may boost clinical confidence, enabling acceptance of kidneys that would otherwise be discarded. We leveraged a novel organ offer simulation platform to conduct a controlled experiment isolating biopsy effects on offer acceptance decisions. Methods Between November 26 and December 14, 2018, 41 kidney transplant surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“… 38 However, the biopsy was impactful to many of the survey respondents: >60% of respondents reported that they would decline a marginal kidney and 46% that they would decline a standard criteria kidney with “bad” histology. The standard criteria donor responses are consistent with a case-based study 39 wherein respondents were provided with a variety of simulated organ offers accompanied by no biopsy, a “poor” biopsy, or a “good” biopsy. The odds of declining an otherwise acceptable kidney from a donor with low serum creatinine but with a “bad” biopsy were 2.5 times that faced by a similar kidney with a “good” biopsy; 31% of the respondents reported that the biopsy prompted them to decline in this situation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“… 38 However, the biopsy was impactful to many of the survey respondents: >60% of respondents reported that they would decline a marginal kidney and 46% that they would decline a standard criteria kidney with “bad” histology. The standard criteria donor responses are consistent with a case-based study 39 wherein respondents were provided with a variety of simulated organ offers accompanied by no biopsy, a “poor” biopsy, or a “good” biopsy. The odds of declining an otherwise acceptable kidney from a donor with low serum creatinine but with a “bad” biopsy were 2.5 times that faced by a similar kidney with a “good” biopsy; 31% of the respondents reported that the biopsy prompted them to decline in this situation.…”
Section: Discussionsupporting
confidence: 56%
“…The odds of declining an otherwise acceptable kidney from a donor with low serum creatinine but with a “bad” biopsy were 2.5 times that faced by a similar kidney with a “good” biopsy; 31% of the respondents reported that the biopsy prompted them to decline in this situation. 39 Similarly, in a national US registry analysis, Lentine et al. 2 found that low-KDPI (<20%) donor organs which were biopsied were >6 times (odds ratio, 6.47) as likely to be discarded as kidneys that were not biopsied.…”
Section: Discussionmentioning
confidence: 98%
“…27 A recent mock offer study on the role of procurement biopsy in acceptance decisions found that offer acceptance rates were significantly influenced by percentage glomerulosclerosis when all other aspects of the biopsy and donor history remained the same. 28 We should also note that while centers continue to use percentage glomerulosclerosis as part of the kidney acceptance decision, the percentage glomerulosclerosis ought to be interpreted within the context of other aspects of donor history, including donor age. A biopsy with 20% glomeruli sclerosed in a kidney from a 20-year-old donor as opposed to a 65-year-old donor have very different prognostic implications, as in the latter instance, the sclerosis may simply reflect age related changes.…”
Section: Discussionmentioning
confidence: 99%
“…All else equal, offer acceptance rates were found to be 37% lower when interstitial fibrosis was reported as mild-moderate compared with absent in a controlled experiment. 21 Our study found that the apparent increased risk associated with interstitial fibrosis is largely, if not entirely, accounted for by other factors. Clinical prediction models statistically adjust for such correlations to avoid the double counting trap.…”
Section: Discussionmentioning
confidence: 53%